Transnational Networks and Intellectual Authority in Islam in Europe: The Case of Mohammed Arkoun, Nasr Hamid Abu Zayd, and Abdolkarim Soroush - Zohouri-Haghian, P (2020)
This thesis explores the socio-political mechanisms that shaped the authority of three Muslim thinkers – Mohammed Arkoun, Nasr Hamid Abu Zayd and Abdolkarim Soroush – in the European-Anglophone intellectual field between 1989 and 2010. Specifically, it investigates the role of transnational networks of individuals and institutions in the intellectual legitimation of these three thinkers. Moving beyond existing literature that focuses on their intellectual contributions, this research situates their discourses within a specific socio-political context. Relying on government papers, newsletters, interviews, bibliometric data, as well as academic and journalistic publications by and about them, the study maps and investigates the modus operandi of their networks. For this purpose, it engages and expands on Pierre Bourdieu’s notion of social capital (resources embedded in an individuals’ network) and field theory, to explore how ‘power’ operates among different fields of interaction to shape their ‘legitimacy’.